Zr(4+)-Doped Anatase TiO(2) Nanotube Array Electrode for Electrocatalytic Reduction of L-cystine - Wang, Weizhen (Materials (Basel), 2020)
A Zr(4+)-doped anatase TiO(2) nanotube array electrode was prepared using a process that included Ti anodizing, chemical immersion, and heat treatment. The compositions, microstructure, and electrochemical properties of the prepared electrodes were characterized. The results show that Zr(4+) was successfully introduced into the TiO(2) nanotube array electrodes. Because Zr(4+) was doped into the crystal structure of the TiO(2)and replaced a part of Ti(4+) to form more oxygen vacancies and Ti(3+), the electrocatalytic activity of the prepared electrodes, for the reduction of L-cystine, was significantly improved.